2017
DOI: 10.1590/1983-21252017v30n312rc
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Inoculated Common Bean in Response to Different Cover Crops and Desiccation Times

Abstract: -The common bean requires high levels of nitrogen (N) to achieve high productivity, which can be supplied, at least partially, by the biological nitrogen fixation (BFN). Two field experiments were carried out in the winter season of 2015 aiming to evaluate the effects of different cover crops, desiccation times and the agronomic performance of the common bean inoculated with rhizobia. The experiments were assembled in a randomized block design with four replications, in a factorial split-plot arrangement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In a study developed by [21], the amount of SDM was influenced by the reinoculation of Rhizobium tropici, corroborating the results found in this study. The increase in bean plant SDM through inoculation was also noted by [22]. Therefore, it can be observed that the use of inoculants can assist in plant development.…”
Section: Development Analysismentioning
confidence: 89%
“…In a study developed by [21], the amount of SDM was influenced by the reinoculation of Rhizobium tropici, corroborating the results found in this study. The increase in bean plant SDM through inoculation was also noted by [22]. Therefore, it can be observed that the use of inoculants can assist in plant development.…”
Section: Development Analysismentioning
confidence: 89%
“…Diversos estudos demonstram maior aproveitamento do nitrogênio e ganhos produtivos na cultura do arroz (SILVA et al, 2016), aumento da fitomassa, gerando aumento na produtividade do milho (Carvalho et al, 2015), redução da infestação de plantas daninhas no cultivo de soja e milheto (Adami et al, 2020), acúmulo de nitrogênio e aumento do desempenho agronômico do feijão-comum (Oliveira et al, 2017), melhorias na fertilidade do solo e incrementos significativos nos teores de nutrientes (P, K + , Mg 2+ e Ca 2+ ) e matéria orgânica do solo (NASCENTE et al, 2015), entre outros.…”
Section: Plantas De Coberturaunclassified
“…Studies with cover crops showed greater use of nitrogen and productive gains in rice (SILVA et al, 2016), increased phytomass and, consequently, corn productivity (CARVALHO et al, 2015), reduction of weed infestation in soybean and millet (ADAMI et al, 2020) and nitrogen accumulation (N) and increased agronomic performance of common bean (OLIVEIRA et al, 2017). Thus, the use of cover crops in agricultural systems has been incorporated as a sustainable strategy, enabling the reduction of the use of agrochemicals and, consequently, production costs, growth and increase in productivity (REZENDE et al, 2021).…”
Section: Introductionmentioning
confidence: 99%